Stock prices of renewable energy firms: Are there asymmetric responses to oil price changes? - Donggyu Lee; Jungho Baek (Economies, 2018)
This article revisits the question of whether crude oil prices have a positive effect on stock the prices of renewable energy firms. To examine this question carefully, we allow for the asymmetric effects of oil price changes in our modeling process, using the nonlinear autoregressive distributed lag (ARDL) approach. We find that changes in oil prices indeed have a significant, positive short-run effect on renewable energy stock prices in an asymmetric manner. However, this short-run effect does not appear to last in the long-run.
Keywords: 330; asymmetry; nonlinear ARDL; oil prices; renewable energy; stock prices